Simulation Study of Silicon Carbide MOSFET based Inverter for Electric Vehicle Application using MATLAB - Mat Mazali, Siti Farah; Razali, Muhammad Anas (Evolution in Electrical and Electronic Engineering, 2021)
Silicon Carbide semiconductor has huge benefits over Silicon semiconductor and is best to apply for inverters in electric vehicle applications. The objective of this study is to develop the Silicon Carbide MOSFET-based inverter while analysing the comparison with the conventional Silicon MOSFET and calculate their loss calculation in the inverter. In this method, the simulation has been done through MATLAB software to construct the Silicon and Silicon Carbide MOSFET model including inverter design. Final outcome of the simulation gave similar results as the previous research. Accordingly, Silicon Carbide MOSFET-based inverter has a lower switching and conduction loss than the Silicon MOSFET-based inverter due to its low on-resistance. This study is best to improve by emphasizing other factors such as adjusting various temperatures to obtain a wider observation on the performance as well as operation of the inverter.